TEMPORAL AND SPACIAL REDUCTION IN CONTEMPORARY IRAQI PAINTING (AN APPLIED STUDY) - Makki Imran Raji, Naseer Kazem Muslim (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The temporal and spatial reduction depends on the prior plan of the artistic work, by choosing the appropriate technology in the formal performance of the oil painting as a technical act that leads to the introduction of an innovative and aesthetic aspect, and the adoption of auxiliary references such as photography, digital design, the principle of sovereignty in the work, and the refinement and simplification of elements and shapes and deleting everything It is overloaded and ineffective.The temporal and spatial reduction depends on a number of natural things, including the psychological action of the same artist on the one hand, and the expression of the essence and idea of the subject, and giving a reflective intellectual aspect to the recipient to complete the vacant places, the empty space reduced, which is the real place, with some reductionist processes of time and place, which help to discipline Simplification and the achievement of deliberate reduction through the verification of the artist’s own experience. The temporal and spatial reduction is subject to external pressurizing provisions and tapes, and the time and place provisions in performance imposed by nature and the cultural institutions that sponsor the preparation of artistic festivals, which is reflected in the performance by the act of temporal and spatial reduction, as a temporal and spatial necessity like other techniques.